Generational Cohorts and Their Collective Memories: An Empirical Study to Develop the Generational Profiling of the Pakistani Workforce - Aliya Ahmad Shaikh; Warda Najeeb Jamal; Syed Muhammad Javed Iqbal; Qurrat Ul Ain Najeeb Jamal (iRASD Journal of Management, 2021)
The current study aims to sociologically categorize the generations of the Pakistani workforce. For this purpose, similar to Schuman and Scott (1989)’s research methodology of identifying generations on the basis of their collective memories of formative events, the current study deploys a quantitative research design. Particularly, this is done by incorporating the socio-economic, political, and technologically significant events (SPTSE) into a questionnaire survey. These events have already been identified as generational pointers of the three Pakistani generations by Shaikh, Jamal, and Iqbal (2021). The Chi-Square results of the current research verify that the Pakistani Baby Boomers (Born during 1942-1961), Pakistani Generation X (Born during 1962-1981), and Pakistani Millennials / Generation Y (Born during 1982-2001) differ in recollecting certain SPTSE which they encountered during their coming-of-age years. Hence, having lived a particular set of formative eras, their generational characteristics, particularly with regard to their attitudes, values, and behaviors, are influenced, which are different and unique from that of the Western generations. This way, the generational pointers serve as a basis for the classification of the three Pakistani generations, and so prove the Asian context-specific application of the theory of generations.